Hipoalbuminemia prabedah sebagai faktor prognostik enterokolitis pascabedah penderita megakolon kongenital (Hirschsprung’s disease) - Rochadi Rochadi (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2013)
Background: Hirschsprung’s disease or congenital megacolon is the congenital absence of ganglion cells in the colon. The rectum is always involved and in 90% of patients the abnormality is confined to the rectum and sigmoid. Absence of ganglion cells prevents peristalsis, resulting in functional obstruction. The success of Hirschsprung’s treatment depends on many factors such as age at the time of operation, body weight, hemoglobin levels, albumin levels, length of operation, length of stay and other prognostic factors. Post operative enterocolitis and other complications still represent as the problem wich often are faced by pediatric surgeons.Objective: The aim of this study was to evaluate the effect of albumin levels on postoperative enterocolitis in children presenting with congenital megacolon.Method: We conducted an ambidirectional cohort study involving children presenting with Hirschsprung’s disease in Dr. Sardjito, Panti Rapih and Permata Husada hospitals in Yogyakarta city from January 2005 to December 2010. All children had been operated using ERPT and PSNRHD methods. The subjects were classified into normoalbuminemia (>3.5 g/dl) and hypoalbuminemia (≤3.5 g/dl). The effect of albumin levels on postoperative enterocolitis were indicated by relative risk and 95% confidence interval.Results: Out of 104 children with Hirschsprung’s disease, 53 (51%) were hypoalbuminemic and 51 (49%) were normoalbuminemia. Postoperative enterocolitis was found in 18 (17.3%) children, 11/18 (61.1%) of them were hypoalbuminemia, whereas 7/18 (38.9%) were normoalbuminemia. Albumin levels were not significant prognostic factor for postoperative enterocolitis in children with congenital megacolon (RR=1.51; 95% CI:0.64-3.60; p=0.34). Conclusion: The albumin levels are not prognostic factor for postoperative enterocolitis in children with congenital megacolon.